Identification and isolation of growth-phase specific proteins of mycobacteria - Bettoni, Jane Clementina (Division of Medical Microbiology, 2017)
The aim of this project was to identify growth phase-specific heat shock proteins of Mycobacterium smegmatis LR222. A growth curve was constructed using the ATP assay. This method was shown by B. A. Ntolosi to be the most accurate indicator of when the organism entered the various phases of growth. It was possible to determine that M. smegmatis LR222 entered the exponential phase of growth after a short lag phase of 4 to 8 hours and persisted in this phase for 20 to 22 hours. It then reached the stationary phase, which lasted for 40 to 46 hours. Protein heat shock assays were performed on growth phase-specific samples. This allowed the identification of a 43-46 kDa in molecular weight stationary phase protein on one-dimensional SOS-PAGE. The protein was induced in cells entering the stationary phase of growth and not by heat shock as it was induced under both the control and the heat shock temperatures. The protein was further characterised by two-dimensional gel electrophoresis, which demonstrated resolution into two, strongly age-associated, proteins. Subtractive RNA hybridisation was attempted in order to obtain a subtraction cDNA probe from a stationary phase RNA sample depleted of sequences common in both the exponential and the stationary phase samples. Ribosomal RNA was removed from the total RNA by the process of photobiotinilation. The mRNA was then used as a template to synthesise with reverse transcriptase single stranded cDNA. cDNA/mRNA denatured hybrids were hybridised to the exponential phase RNA sample. The new hybrids were "subtracted" by chemical cross-linking with DZQ and the unique cDNA used to produce by random primers a radioactively labelled probe. A M. smegmatis library was probed but unfortunately no signal was observed. Further adjustments and improvements to this technique are required before it can be used effectively.